Keselerasan Kebijakan, Perencanaan, dan Standar Teknologi Informasi terhadap Strategi Teknologi Informasi pada Instansi Pemerintah - Ardi Hamzah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
Alligment of information technology policy, planning, and standard on information technology strategy atgoverment institution form a model that must implementated. Information technology policy form combineconcept and fundament that become reference and plan fundament in conducting a working, leading, and wayreaction at goverment institution. Planning form process, way and acting to design of these policy so that stepappropriate with the objectives that targeted. The standard form certained size that used as reference.Technology policy that explained in information technology planning and standard will appereance informationtechnology strategy framework. These framework will appereance: (i) services validity; (ii) creating of systemthat comprehensive and integrated; (iii) optimalizatation of technology benefit; and (iv) benefit of businessworld potency.Keywords: Information Technology, Policy, Planning, Standard, Strategy